Advances in the Management of Children and Adolescents with Obesity - Manuel Reig García-Galbis; Rosa María Martínez-Espinosa (Children)
Obesity is a frequent, severe, complex, recurrent, and chronic disease characterized by an excessive accumulation of fat, which can have negative effects on health and decrease life expectancy [...]